Islamic Values and Gen Z's Investment Behavior in the Sharia Stock Market: Beyond Rationality - Achmad Agus Priyono; Ety Saraswati; Agus Widarko (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
This study explores how financial literacy and risk perception impact Sharia stock investment decisions among Generation Z students, with Islamic values as a moderator variable. The urgency of this research arises from the relatively slow growth of Sharia investors in Indonesia, which only accounted for 2.6% of total stock market investors in November 2023, even though Generation Z represents the majority of new investors. The quantitative explanatory research design was applied by surveying 130 students from the Faculty of Economics and Business, Islamic University of Malang, active in the Sharia Investment Gallery. The data were analyzed using Partial Least Squares–Structural Equation Modeling with WarpPLS software. The findings revealed that financial literacy and Islamic values significantly influenced Sharia stock investment decisions, while risk perception did not show a significant effect. Moreover, moderation analysis shows that Islamic values do not strengthen the relationship between independent variables and investment decisions but serve as direct determinants. The novelty of this study shows that, in a context with high religious homogeneity, Islamic values operate as internalized standards that shape investment behavior. These insights advance Islamic Behavioral Finance and inform policies on Islamic financial literacy and sustainable capital market development.